2020
DOI: 10.13106/jafeb.2020.vol7.no9.117
|View full text |Cite
|
Sign up to set email alerts
|

Tests of a Four-Factor Asset Pricing Model: The Stock Exchange of Thailand

Abstract: The objective of this study is to examine whether the four-factor model explains variation in the expected return of stocks on the Stock Exchange of Thailand. The study used individual monthly data for all stock with continuous trading on the Stock Exchange of Thailand. The study used sample data of 429 listed stocks to construct 8 portfolios bases on the industries. In this study, subject to market factors such as size, the book-to-market ratio, the market beta, and stock liquidity are taken into account. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Moreover, a considerable quantity of research studies has made substantial contributions in the discipline of APM by postulating the determinants of expected stock returns and capturing capability of associated risk premiums. Davidson et al (2002); Fama and French (1993) argued that firm-specific fundamental variables such as firm size, B|M ratio, dividend yield, momentum capture implicit risk measures which investors demand to be compensated as reward of bearing risks that explain the variation in stock returns, (Pojanavatee, 2020;Shaharuddin et al, 2018;Acheampong & Swanzy, 2016;Lau et al, 2002). Based on beta analysis, there are two versions of CAPM findings such as static OLS where beta coefficient is considered to be constant over time and alternative is time varying beta coefficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, a considerable quantity of research studies has made substantial contributions in the discipline of APM by postulating the determinants of expected stock returns and capturing capability of associated risk premiums. Davidson et al (2002); Fama and French (1993) argued that firm-specific fundamental variables such as firm size, B|M ratio, dividend yield, momentum capture implicit risk measures which investors demand to be compensated as reward of bearing risks that explain the variation in stock returns, (Pojanavatee, 2020;Shaharuddin et al, 2018;Acheampong & Swanzy, 2016;Lau et al, 2002). Based on beta analysis, there are two versions of CAPM findings such as static OLS where beta coefficient is considered to be constant over time and alternative is time varying beta coefficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the theoretical failure of this model as well as its failure to capture anomalies such as size, book-tomarket and long-term past returns, till now, most financial managers in the U.S and all over the world are still using this model because it depends on one parameter (beta) and is relatively straightforward compared to any other model. On the Stock Exchange of Thailand, Pojanavatee (2020) showed that systematic risk measured by the beta coefficient did play a significantly crucial role in the prediction and formation of the rate of return. Phuoc, Kim and Su (2018) found that the robust Trimmed Square (LTS) gives more accurate estimate than the Ordinary Least Square (OLS) and daily return data provide much better estimate than monthly return data.…”
Section: Traditional Stagesmentioning
confidence: 99%
“…The level of risk is indicated by the variable β (beta) and return is stated to have a positive and linear relationship with that variable. The higher the β of a stock shows, the greater the risk contained in it and will affect the increase in return (Pojanavatee, 2020).…”
mentioning
confidence: 99%